AN INTRODUCTION TO GROUND PENETRATING RADAR (GPR) IN SEDIMENTS - Bristow C.S.; Jol H.M. (My University, 2003)
In sedimentary geology, ground penetrating radar (GPR) is used primarily for stratigraphic studies where near-continuous, high-resolution profiles aid in determining: (1) stratigraphic architecture, (2) sand-body geometry, and (3) correlation and quantification of sedimentary structures. In the past, to investigate lateral continuity and variability of sediments, we had to infer the correlation between boreholes, outcrops or shallow trenches.